Tail Dependence and Systemic Risk in Operational Losses of the US Banking Industry*. (14th February 2017) - Abdymomunov, Azamat; Ergen, Ibrahim
Abstract: Using supervisory operational loss data of the US banking industry, we analyze dependence among operational losses within banks and across banks. We find evidence of relatively strong dependence among tail losses of different operational loss types within banks. Applying a copula framework, we estimate that the median correlation parameter for the key operational loss types is around 30% and exceeds 50% for some banks in our sample. Our results contrast with the previous literature that documents that correlation parameter estimates are in the range of 5–10% and typically do not exceed 20%. Further, we demonstrate significant model risk from not accounting for dependence among tail losses, resulting in material underestimation of operational risk. In addition, we investigate dependence of operational losses across banks. Using a copula framework, we estimate correlation parameters between losses of large banks in our sample to be 42% on average. This result suggests the presence of systemic risk from the simultaneous occurrence of operational tail losses in different large banks.